Excellence in Cardiovascular Sciences Program at Wake Forest School of Medicine. - Tallant, E. Ann; Diz, Debra I. (Journal of Best Practices in Health Professions Diversity: Education, Research & Policy)
The Excellence in Cardiovascular Sciences (EICS) program at Wake Forest School of Medicine (WFSM) provides short-term research training on the cardiovascular system for undergraduate students of diverse backgrounds. Continuously funded by the National Heart, Lung, and Blood Institute since 1992 (R25 HL092618), it is housed in the WFSM Hypertension & Vascular Research Center. Participants--12 students who matriculate at undergraduate institutions throughout the United States and Puerto Rico--are from minority and/ or disadvantaged backgrounds or have disabilities and wish to pursue a biomedical research career. For 8-9 weeks each summer, they conduct biomedical research in the laboratories of mentors with expertise in hypertension, cardiovascular diseases, atherosclerosis, diabetes, obesity, and vascular disease. They learn to evaluate the scientific literature and make scientific presentations; about careers in the biomedical sciences; and establish links with faculty mentors who foster their continued interest in biomedical research. Over 80 percent of former participants who finished their undergraduate degrees from 1993-2012 attained graduate, medical, or industrial technical positions. Over 37 percent received PhD or Master's Degrees; 30 percent are health professionals; and 14 percent participate in industry or technical positions. Furthermore, approximately 15 percent have continued their association with WFSM as PhD, medical, or technical/postbaccalaureate students. In fact, 20 percent of the underrepresented minority students awarded PhDs by our biomedical sciences programs from 2009-2011 participated in the EICS program. These statistics demonstrate its continued success in providing training to facilitate the matriculation of underrepresented minority students into postgraduate studies and careers in biomedical research.